STUDENTS’ RESPONSE TO SCHEMA THEORY APPLIED IN WRITING CLASS FOREIGN LANGUAGE LEARNING - SOFI YUNIANTI (Universitas 17 Agustus 1945 Surabaya, 2018)
Much research analyzed the application of schema theory in classroom. However, few research have discussed about students’ response in writing class that applied schema theory, especially in Foreign Language Class. This research aims to find students’ response applied schema theory in writing class foreign language learning. It discovers what student’s opinion to the schema application in writing class. Finally, it discusses the implication of the research’s finding towards the schema theory, and encourages further study relating different groups of students in different contexts. Keywords Writing, Schema Theory, Foreign Language Learning